Deletion of murine Rhoh leads to de-repression of Bcl-6 via decreased KAISO levels and accelerates a malignancy phenotype in a murine model of lymphoma. (31st December 2022) - Horiguchi, Hiroto; Xu, Haiming; Duvert, Beatrice; Ciuculescu, Felicia; Yao, Qiuming; Sinha, Amit; McGuinness, Meaghan; Harris, Chad; Brendel, Christian; Troeger, Anja; Chiarle, Roberto; Williams, David A.
ABSTRACT: RHOH/TFF, a member of the RAS GTPase super family, has important functions in lymphopoiesis and proximal T cell receptor signalling and has been implicated in a variety of leukaemias and lymphomas. RHOH was initially identified as a translocation partner with BCL-6 in non-Hodgkin lymphoma (NHL), and aberrant somatic hypermutation (SHM) in the 5ʹ untranslated region of the RHOH gene has also been detected in Diffuse Large B-Cell Lymphoma (DLBCL). Recent data suggest a correlation between RhoH expression and disease progression in Acute Myeloid Leukaemia (AML). However, the effects of RHOH mutations and translocations on RhoH expression and malignant transformation remain unknown. We found that aged Rhoh −/− (KO) mice had shortened lifespans and developed B cell derived splenomegaly with an increased Bcl-6 expression profile in splenocytes. We utilized a murine model of Bcl-6 driven DLBCL to further explore the role of RhoH in malignant behaviour by crossing Rhoh KO mice with Iµ-HABcl-6 transgenic (Bcl-6 Tg ) mice. The loss of Rhoh in Bcl-6 Tg mice led to a more rapid disease progression. Mechanistically, we demonstrated that deletion of Rhoh in these murine lymphoma cells was associated with decreased levels of the RhoH binding partner KAISO, a dual-specific Zinc finger transcription factor, de-repression of KAISO target Bcl-6, and downregulation of the BCL-6 target Blimp-1. Re-expression of RhoH in Rhoh KO Bcl-6 Tg lymphoma cell lines reversed these changes in expression profile and reduced proliferation of lymphoma cells in vitro. These findings suggest a previously unidentified regulatory role of RhoH in the proliferation of tumour cells via altered BCL-6 expression. (250)